Rational Phytotherapy A Physicians’ Guide to Herbal Medicine - Schulz, Volker; Hänsel, Rudolf; Tyler, Varro E. (Springer Berlin Heidelberg, 1998)
Rational Phytotherapy adds a truly significant dimension to the practice of science-based herbal medicine. Detailed examination of the original German edition led to the conclusion that the book simply had to be translated into English to make the valuable information it contained available to a broader audience. That desire has now been realized, and the results of scientific studies and clinical trials of therapeutically use ful botanical drugs are now placed before interested readers in the uni versallanguage of science. Even the most cursory acquaintance with phytotherapy, herbal treat ment, botanical medicine - whatever you choose to call it - causes one to recognize that throughout most of the world, and especially in the United States and the United Kingdom, the practice is at best an imper fect art. In Germany, the use of plant drugs is a science. There are many reasons for this. Tradition can certainly not be discounted. However, the principal reason is, without question, the enlightened system of laws and regulations governing the sale and use of such products in that country